2004
DOI: 10.1111/j.1365-2265.2004.02086.x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal regulation of thirst and vasopressin secretion following surgery for craniopharyngioma

Abstract: This study demonstrates following surgery for craniopharyngioma there is a high incidence of cranial diabetes insipidus and a significant incidence of abnormal thirst responses to osmotic stimuli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 24 publications
2
45
0
Order By: Relevance
“…We further evaluated causes of hypopituitarism and considered only cases where posterior pituitary damage was likely. 30,31 The following cases were excluded: subclinical hypopituitarism (n ¼ 16); 4,6,8,11 -13,17,19,25,28,29 cause of hypopituitarism not specified (n ¼ 1); 21 first-trimester miscarriages (n ¼ 15). 1,4,12,19 Sixteen case reports 3,5-7,9,10,14 -16,18,20,22-24,26,27 describing the outcome of 18 pregnancies and one trial 1 reporting 13 pregnancies in nine women were included in the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…We further evaluated causes of hypopituitarism and considered only cases where posterior pituitary damage was likely. 30,31 The following cases were excluded: subclinical hypopituitarism (n ¼ 16); 4,6,8,11 -13,17,19,25,28,29 cause of hypopituitarism not specified (n ¼ 1); 21 first-trimester miscarriages (n ¼ 15). 1,4,12,19 Sixteen case reports 3,5-7,9,10,14 -16,18,20,22-24,26,27 describing the outcome of 18 pregnancies and one trial 1 reporting 13 pregnancies in nine women were included in the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Smith et al (31) reported absence of thirst in 19% of adults with DI treated with surgery combined or not with CRT. A loss of temperature control (very low temperature) was recorded in adult CP patients after surgery for a CP (32).…”
Section: Thirst Disorder Thermoregulatory Disorders Somnolence and mentioning
confidence: 99%
“…If the diagnosis of adipsic DI was suggested clinically and by the results of thirst visual analogue scale applied to the WDT, the formal diagnosis of adipsic DI was confirmed by thirst and AVP responses to the i.v. infusion of hypertonic saline (855 nmol/l), as previously described by Smith et al (9) in our centre.…”
Section: Diagnosis and Definition Of Abnormalitiesmentioning
confidence: 99%